HUBUNGAN KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN REGULASI DIRI DALAM BELAJAR (SELF-REGULATED LEARNING) TERHADAP HASIL UJIAN OSCA MAHASISWA KEBIDANAN STIKES MEGA REZKY MAKASSAR - Alkautzar, Anieq Mumthi’ah (Journal of Islamic Nursing, 2018)
OSCA method given in midwifery education with the aim of a midwife being able to have the professional competence of miasertydwives to be possessed of the cognitive, affective and psychomotor in providing midwifery care .The research aimed to investigate the correlation of the emotional intelligence, spiritual intelligence and Self-regulated learning with OSCA test results of DIII Midwifery student. This research type was observational and analytical with the cross sectional design. The research population comprised 330 fourth year DIII Midwifery students of STIKES Mega Resky Makassar, and from them 116 students had been chosen as samples by using the systematic sampling technique. The research results revealed that all independent variables with the value of Asymp.Sig value. (two sided) showed 0.000 (P <0.05), meaning that each variable had a significant correlation with the dependent variables in the model. Based on the result of the layer analysis, it was found that the spiritual intelligence had a simultaneous and significant contribution on the results of OSCA test.